Pengaruh Senam Kegel terhadap Penyembuhan Luka Perineum pada Ibu Post Partum - Ratna Budi Purwaningrum; Ita Herawati (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
WHO data in 2017 shows that every day, an average of 830 women die during pregnancy and after childbirth. MMR in Indonesia in 2020 fell to 230/100,000 live births. Maternal mortality during the puerperium was caused by puerperal infection (10.0%), occurred due to lack of care for perineal wounds, bleeding (42%) caused by tearing of the birth canal, remnants of the placenta and uterine antonia, eclampsia (13%) and complications during pregnancy. postpartum (11%). Effective mobilization for postpartum women in accelerating the healing process of perineal wounds is by doing Kegel exercises, including improving blood circulation, updating body posture, improving pelvic/pelvic floor muscles of a woman. Objective of this study is knowing the effect of Kegel exercises on perineal wound healing in post partum mothers. Quasi experiment with posttest only control group design were used in this study. The sample in this study were all post partum mothers in February-March 2022 as many as 20 people (total sampling). The average perineal wound healing in the intervention group was 5.30 and in the control group was 7.80. There is an effect of Kegel exercises on perineal wound healing in post partum mothers at BPM Nunung Nurhikmah Bekasi in 2022 (p value 0.000). There is an effect of Kegel exercises on perineal wound healing in postpartum mothers at BPM Nunung Nurhikmah Bekasi in 2022. Midwives are expected to provide counseling to postpartum mothers to do Kegel exercises so that perineal wound healing can be faster.